Hydrogen sensing characteristics of a Pd/Nickel oxide/GaN-based Schottky diode. (1st March 2019) - Liu, I-Ping; Chang, Ching-Hong; Huang, Yen-Ming; Lin, Kun-Wei
Abstract: Hydrogen sensing characteristics of a novel metal-oxide-semiconductor (MOS) Schottky diode are thoroughly investigated. The MOS structure consists of a gallium nitride (GaN)-based semiconductor system, a nickel oxide (NiO) layer, and palladium (Pd) catalytic materials. A well-prepared Pd/NiO/GaN-based diode shows several advantages in relation to hydrogen sensing, including a simple structure, high sensing speed, wide flexibility for operation under both forward and reverse applied voltages, and a good sensing response of 8.1 × 10 3 under an applied forward voltage of 0.25 V, at 300 K in a 1% H2 /air ambience. Furthermore, under an applied reverse voltage of −2 V and at a high temperature of 573 K, this MOS diode shows a response as high as 1.8 × 10 4 towards 1% H2 /air mixture gas. The Schottky diode sensor with a novel Pd/NiO/GaN structure demonstrated in this study is a promising candidate for high-performance hydrogen sensing applications. Highlights: The introduction of a NiO layer of this hydrogen sensor can suppress the reversed leakage current effectively. A high sensing response of 8.1 × 10 3 is obtained under a forward voltage of 0.25 V, 1% H2 at 300 K. A remarkably high sensing response of 1.8 × 10 4 is found under a reversed voltage of -2 V, 1% H2 at 300 K. The studied hydrogen sensing device exhibits high sensing speed, wide operating temperature.